Hic sunt leones. Iconographic analysis and computational modelling for the study of the Iron Age free-standing lions of the Elbistan plain (south-eastern Anatolia) - Francesco Di Filippo; Federico Manuelli (Asia Anteriore Antica)
Lying between the central Anatolian plateau and the Euphrates region, the Elbistan plain represents an ideal environment for inspecting forms of cultural interconnection. During the Iron Age, this territory was marked by the presence of notable inscribed monuments, the study of which allowed scholars to establish relationships with the most significant Neo-Hittite dynasties. This region is also characterized by the presence of sets of anepigraphic portal lions, positioned seemingly at random in the open landscape and with no apparent relationship with coeval archaeological remains, which have never been concretely integrated into the historical picture. In this contribution, the iconographic and stylistic analysis of these sculptures will allow us to situate them in their chronological and historical framework. A computational spatial model is further used to evaluate the meaning of their positioning as markers of a visual networking system that may have represented the most significant thoroughfares to and from the Elbistan plain.